Gestión del recurso pluvial en el campus de la Universidad América: Estudio de modelos de recolección (2016)
The paper reviews from design variables, chemical storage conditions and economic costs, different models, national and international, rainwater harvesting. Comparing the advantages and disadvantages in order to review the behavior of these models, and to find the common and appropriate elements that allow their use in the campus of Universidad América.